Poor People in a Rich Country : Volume 1. Poverty Report for Argentina - World Bank (Washington, DC, 2013)
The study presents an overview on Argentina's economic growth, income distribution, and poverty, mostly as of 1991, when the country underwent a period of adjustment, which remarkably led to a sharp inflation drop, to the privatization of state-owned industries, and to fostering foreign commerce, thus widening the economy. Nonetheless, the study points out that all of these adjustments affected the poor, particularly through labor demand, exacerbated by the slowdown of the growth process, resulting from the economic crises of 1995, and 1998. Recommendations include macroeconomic, and reform policies to allow rapid growth, and stabilize the economy, without inflation, for a substantial poverty reduction. The elimination of centralized, collective bargaining labor agreements, reduction of labor taxes, and severance payments, would prod a funded, unemployment insurance system, based on individual accounts, and thus, reduce the high cost of labor. Temporary employment, and extended programs should not be enforced under payroll taxes, to allow exceptions for small scale enterprise development. Accessibility of the poor to basic services should be enhanced, mainly through greater investments in education, and health care services. In addition, a strong system of safety nets is recommended, through the identification of expanding programs, to also provide emergency employment, and income during potential crises.